Positioning textile repair: Viewing a culture of perfection through surface imperfections - Yolanta Gale; Debra Lilley; Garrath Wilson (2020)
The practice of early disposal and trigger-happy purchasing practices are examples of a seemingly illogical response to no longer desired products. Current behaviour toward surface and product imperfections is representative of an endemic issue in the development of negative attitudes and culture towards imperfection, in order to address negative material concerns and habits associated with textile products, the connection between internally projected expectations of perfection need to be considered in conjunction with externally projected ideals. This paper examines the relationship between current adversities to textile imperfections and concepts of human imperfection. It positions the potential role that repair activity can have in addressing the current culture of perfection in textile surfaces.